Air Two-Phase Flow Void Fraction – Water and Oil Emulsion on Mini Pipe with a slope of 600 Against Horizontal Position - Sukamta Sukamta (Universitas Muhammadiyah Yogyakarta, 2022)
The utilization of two-phase or multi-component flow in mini pipes is often found in the industrial world, such as mini evaporators, mini heat exchangers, etc. Multi-component flow can also be found in the biomedical, such as in the human circulatory system through vessels. An important parameter in a two-phase flow is the hollow fraction since this parameter significantly affects the flow pattern, which affects pressure fluctuations. Therefore, this study aims to obtain primary experimental data on the vacuum fraction, specifically in the air flow-water and oil emulsions with concentrations of 350 mg/dl and 500 mg/dl at an inclination of 60o to the horizontal. The study used a glass pipe with a diameter of 1.6 mm and a length of 160 mm. Data were captured using a high-speed camera at a gas superficial velocity (JG) = 0.083 m/s - 74.604 m/s and the superficial velocity of the liquid (JL) = 0.041 m/s - 4.145 m/s, and processed using MATLAB R2014a software. The results showed that the difference in the concentration of water and oil emulsions significantly affects the void fraction value, thus affecting the flow pattern. This case is because the difference in the concentration of water and oil emulsions affects the viscosity value, ultimately affecting the liquid's superficial velocity. Similarly, the slope of the pipe 60o to the horizontal affects the flow pattern that occurs; this is because the slope of the pipe will cause the influence of gravitational acceleration on the value of the superficial velocity of gases and liquids, although not very significant. The rise and fall of the gas's superficial velocity and the liquid's superficial velocity affect the value of the hollow fraction. More plug, slug-annular, annular, and churn flow patterns were identified than bubbly flow patterns, which is why the hollow fraction increased with the gas's superficial velocity and decreased with low superficial velocity. This kind of flow pattern needs to be watched out for because it has the potential to increase pressure significantly.